Grundtvig and John Wesley – A Study of Convergence in Their Theologies - Thaarup, Jørgen (Grundtvig-Studier, 2019)
John Wesley (1703-1791) and Nicolai Frederik Severin Grundtvig (1783-1872) were two very influential theologians, Wesley in eighteenth-century Anglican England and Grundtvig in nineteenth-century Lutheran Denmark.1 They became reformers of the Protestant concept of Christian thinking within their respective contexts of church and society. Wesley’s theological ideas and ecclesiastical initiatives have spread internationally, forming and influencing new churches, schools, hospitals, and universities in many countries. Grundtvig’s ideas have inspired theological and pedagogical understanding not only in Denmark but also, more broadly, in Scandinavia and internationally.